Nesfatin-1 alleviates gastric damage via direct antioxidant mechanisms - YEGEN, BERRAK; ŞİRVANCI, SERAP; ÖZDEMİR KUMRAL, ZARİFE NİGAR (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2015)
Background: Indomethacin is a nonsteroidal anti-inflammatory drug, which is known to produce serious side effects, causing ulcerative lesions. Nesfatin-1, a newly identified anorexigenic peptide, was recently shown to have neuroprotective effects. The aim of the study was to investigate the anti-inflammatory effects of nesfatin-1 on indomethacin-induced gastric ulcer. Materials and methods: After a 24-h starvation period, ulcer was induced in Sprague-Dawley rats by subcutaneous administration of indomethacin (25 mg/kg), whereas control group received vehicle. Fifteen minutes after ulcer induction, rats were treated with either saline or nesfatin-1 (0.1, 0.3, or 1 mu g/kg, intraperitoneally). At the fourth hour, all rats were decapitated and their trunk blood was collected for tumor necrosis factor (TNF)-alpha and interleukin (IL)-6 measurements. Stomach samples were examined microscopically and analyzed for myeloperoxidase (MPO) activity, malondialdehyde (MDA), glutathione (GSH), luminol-, and lucigenin-enhanced chemiluminescence (CL) levels. Results: Ulcer induction increased serum TNF-alpha; and IL-6 levels, gastric CL and MDA levels and MPO activity but decreased gastric GSH content (P < 0.05-0.001). On the other hand, 0.1 mu g/kg dose of nesfatin-1 reduced microscopic and macroscopic damage scores, decreased MPO activity and MDA levels, CL and IL-6 levels, whereas gastric GSH was replenished (P < 0.01). However, indomethacin-induced increase in TNF-alpha level was abolished at only 1 mu g/kg dose of nesfatin-1 (P < 0.01). Conclusions: Nesfatin-1 alleviated indomethacin-induced gastric injury, suggesting that the anti-inflammatory and gastroprotective effects of nesfatin-1 on oxidative gastric damage could be implemented by supporting the balance in oxidant and antioxidant systems while inhibiting the generation of pro-inflammatory mediators. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Ulcer; Indomethacin; Nesfatin-1; Gastric damage; Antioxidant; TUMOR-NECROSIS-FACTOR; FREE-RADICALS; NITRIC-OXIDE; INDOMETHACIN; INJURY; RAT; INFILTRATION; PATHOGENESIS; INFLAMMATION; GLUTATHIONE